1996
DOI: 10.1046/j.1365-2265.1996.668489.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between serum interleukin‐6 and thyroid hormone concentrations in 270 hospital in‐patients with non‐thyroidal illness

Abstract: Our data revealed a statistical relation between elevated serum IL-6 concentrations and alterations in circulating thyroid hormone concentrations seen in NTI; however, the findings in patients with renal disease suggest that circulating IL-6 is not the only factor responsible for alteration in thyroid hormone metabolism in NTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
46
0
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 0 publications
12
46
0
7
Order By: Relevance
“…IL-6 levels were elevated in serum of all NTI patients and correlated strongly with serum T 3 , which is in agreement with previous reports (Boelen et al 1993, Davies et al 1996. IL-6 has been shown to contribute to the pathogenesis of NTI but the mechanisms have not yet been elucidated (Boelen et al 1996).…”
Section: supporting
confidence: 81%
“…IL-6 levels were elevated in serum of all NTI patients and correlated strongly with serum T 3 , which is in agreement with previous reports (Boelen et al 1993, Davies et al 1996. IL-6 has been shown to contribute to the pathogenesis of NTI but the mechanisms have not yet been elucidated (Boelen et al 1996).…”
Section: supporting
confidence: 81%
“…Pro-inflammatory cytokines such as tumour necrosis factor-α [24], interleukin-1 [25] and 6 (IL-6) [26] have a major role in thyroid hormone imbalances. Serum IL-6 levels are often increased in NTIS and have been inversely correlated with T3 levels and TSH suppression [27]. The C-reactive protein is an inflammatory protein used in clinical decision-making produced by the liver in response to IL-6 [20].…”
Section: Discussionmentioning
confidence: 99%
“…A temporal relationship between IL-6 and thyroid hormone variations was observed in the post-surgery period, since the increase in serum IL-6 concentration occurred early and preceded the decrease in serum T 3 concentration both in adults (91) and in children undergoing cardiopulmonary bypass (92). A recent evaluation of 270 inpatients with NTI, while confirming changes in IL-6 levels and their relationship with variations in serum thyroid hormone concentrations, showed that the IL-6 increase was modest in patients with acute or chronic renal disorders, in spite of the concomitant decrease in serum thyroid hormone concentrations, suggesting that, at least in this form of NTI, IL-6 is not the only or most important causative factor responsible for alterations in thyroid hormone metabolism (93).…”
Section: European Journal Of Endocrinology (1998) 138mentioning
confidence: 99%